Surgical Treatment Efficiency Of Patients With Scar Strictures In Extrahepatic Ducts Using Superelastic Titanium Nickelide Constructions (Journal of Pharmaceutical Negative Results, 2022)
Over the past few decades, there have been significant changes in the prevention, diagnosis and treatment of many complications of abdominal surgery, including cicatricle strictures of the extrahepatic ducts, thanks to constantly evolving medical technologies. Nevertheless, the treatment of cicatricle strictures in extrahepatic bile ducts remains as difficult task that requires great experience and skill of surgeon. Introduction of superelastic titanium nickelide structures with a memory effect was another step in the development of reconstructive hepatobiliary surgery. This work aims to identify the effectiveness of surgical treatment of patients with cicatricle strictures of the extrahepatic ducts using superelastic titanium nickelide structures. Materials and methods: a retrospective analysis of the case histories of 81 patients with cicatricial strictures of the extrahepatic bile ducts was carried out. Depending on the method of surgical intervention, all patients were divided into 2 clinical groups depending on the method of surgical treatment. Long-term results of surgical treatment in the form of quality of life were assessed using MOS SF - 36 (Medical Outcomes Study Short Form 36) and GSRS (Gastrointestinal Simptom Rating Scale) upon patient admission to the hospital, 1, 3, 6, 12 months after surgery and in long-term periods (from 2 to 7 years). Statistical processing of the material was carried out using Excel 7.0 for Windows XP, Statistika for Windows 6.0. The significance of differences in mean values was determined based on Student's t-criteria. Results: on all SF-36 scales, the comparison group showed a significant decrease in the quality of life compared to the main group (p <0.001). In patients of the main group, physical and mental components of health are higher than in patients of comparison group. In patients of the comparison group, in the long-term period, GSRS indicators (especially abdominal pain syndrome, reflux syndrome, dyspeptic syndrome) in total significantly (p <0.05) have higher values compared to the main group. And according to the scales of constipation syndrome and diarrheal syndrome, the differences are not significant (p>0.05). Conclusions: in patients of the main group, who received titanium nickelide stents, in the long-term period, the life quality is higher than in patients of the comparison group operated on by traditional methods (according to the general SF-36 and specific GSRS questionnaires).